(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
From 1988 to 1995 faunistic and applied studies were carried out on Chironomids (Diptera: Chironomidae) in four rice-fields in North-eastem ltaly; some of these species are pests of the rice crop. In this second contribution to the knowledge of rice-field Chironomids, all the genera and species found throughout the eight years of survey are reported; moreover, a key for the identification of the larvae, pupae and adult males is proposed. The area object of most investigation is the southem Veronese plain. In total, 43 taxa were found 8 of which belonging to the subfamily Tanypodinae, 9 to the Orthocladiinae and 26 to the Chironominae. Ali taxa are mostly typical of a slow running or stagnant water habitat. Short ecological notes of nine species, very frequently found, are included.